Comparative Cell Surface Proteomic Analysis of the Primary Human T Cell and Monocyte Responses to Type I Interferon - Soday, Lior; Potts, Martin; Hunter, Leah M.; Ravenhill, Benjamin J.; Houghton, Jack W.; Williamson, James C.; Antrobus, Robin; Wills, Mark R.; Matheson, Nicholas J.; Weekes, Michael P. (Frontiers in Immunology, 2021)
The cellular response to interferon (IFN) is essential for antiviral immunity, IFN-based therapy and IFN-related disease. The plasma membrane (PM) provides a critical interface between the cell and its environment, and is the initial portal of entry for viruses. Nonetheless, the effect of IFN on PM proteins is surprisingly poorly understood, and has not been systematically investigated in primary immune cells. Here, we use multiplexed proteomics to quantify IFNα2a-stimulated PM protein changes in primary human CD14+ monocytes and CD4+ T cells from five donors, quantifying 606 and 482 PM proteins respectively. Comparison of cell surface proteomes revealed a remarkable invariance between donors in the overall composition of the cell surface from each cell type, but a marked donor-to-donor variability in the effects of IFNα2a. Furthermore, whereas only 2.7% of quantified proteins were consistently upregulated by IFNα2a at the surface of CD4+ T cells, 6.8% of proteins were consistently upregulated in primary monocytes, suggesting that the magnitude of the IFNα2a response varies according to cell type. Amongst these differentially regulated proteins, we found the viral target Endothelin-converting enzyme 1 (ECE1) to be an IFNα2a-stimulated protein exclusively upregulated at the surface of CD4+ T cells. We therefore provide a comprehensive map of the cell surface of IFNα2a-stimulated primary human immune cells, including previously uncharacterised interferon stimulated genes (ISGs) and candidate antiviral factors.